Observations of Infection Structures after Inoculation with Colletotrichum orbiculare on the Leaves of Cucumber Plants Pre-inoculated with Two Bacterial Strains Pseudomonas putida or Micrococcus luteus - Jeun, Yong-Chull (The Korean Society of Mycology, 2005)
Infection structures were observed at the penetration sites on the leaves of cucumber plants inoculated with Colletotrichum orbiculare using a fluorescence microscope. The cucumber plants were previously drenched with suspension of bacterial strains Pseudomonas putida or Micrococcus luteus. The plants pre-inoculated with both bacterial strains were resistant against anthracnose after inoculation with C. orbiculare. To investigate the resistance mechanism by both bacterial strains, the surface of infected leaves was observed at the different time after challenge inoculation. At 3 days after inoculation there were no differences in the germination and appressorium formation of conidia of C. orbiculare as well as in the callose formation of the plants between both bacteria pre-inoculated and non-treated. At 5 days, the germination and appressorium formation of the fungal conidia were, however, significantly decreased on the leaves of plants pre-inoculated with M. luteus at the concentration with 1.0 × 10(7) cfu/ml. Furthermore, callose formation of plants cells at the penetration sites was apparently increased. In contrast, there were no defense reactions of the plants at the concentration with 1.0 × 10(6) cfu/ml of M. luteus. Similarly, inoculation P. putida caused no plant resistance at the low concentration, whereas increase of callose formation was observed at the higher concentration. The results of this study suggest that the resistant mechanisms might be differently expressed by the concentration of pre-treatment with bacterial suspension.